TACTICS OF SOLIDARITY IN THE IMPLEMENTATION OF A COMMUNICATIVE STRATEGY OF PERSUASION IN THE PREACHING DISCOURSE - ZELINSKA, O. (Linguistic Bulletin (Movoznavchyi Visnyk), 2022)
Introduction. In recent decades, there have been clear trends in the study of pragmatic aspects of the communicative process in the sacred sphere. Ukrainian linguists, grounding on the significant achievements of foreign scholars, are actively studying the communicative strategies of the language influence and the tactics of their implementation. Less studied in this aspect is the religious discourse, in particular preaching, which determines the relevance of the proposed work. The purpose of the article is to describe the linguistic methods of implementing the tactics of solidarity in the preaching discourse. The texts of sermons of the Ukrainian religious figures of the Orthodox, Catholic and Greek Catholic denominations, as well as congratulatory and pastoral messages, solemn speeches have become the material of the research. Results. A sermon belongs to the varieties of the institutional religious discourse. The specifics of the communicative situation in the preaching discourse has a hierarchical character, it is due to the higher status of the preacher as a religious figure. The main communication strategy used by the preacher is the strategy of persuasion. Through persuasion, the priest must affirm or convert the addressee in the faith, affirm Christian values, encourage to follow the norms of Christian morality or compel him to change his behavior if it does not conform to it. In order to implement a convincing influence on the addressee in the preaching discourse, the authors of sermons actively use the language tactics of solidarity, which is aimed at rapprochement with the addressee, leveling the distance between the speaker-preacher and the addressees – the faithful, creating a trusting atmosphere. At the heart of the tactics is a person’s mental need to be among likeminded people, to be among equals, to belong to the circle of “their own”. Linguistic methods of implementing the tactics of solidarity during preaching are the messaging of information about commonality with the addressee, the belonging to the Christian community, confession of the same values, the same episodes from the past, the same prospects for the future. Preachers productively use the technique of connecting the audience to a joint action at all stages of speech, as a result of which the recipients realize themselves as co-creators of the sermon. Close tactics with the audience is facilitated by the tactics of openly declaring the desire to support each of the believers in difficult life situations, the desire to understand and help to correct life’s mistakes. The tool for implementing the tactics in each case is the skillful use of the Ukrainian language resources at different language levels. Conclusion. An important tool for implementing the strategy of persuasion in the preaching discourse is the tactics of solidarity with the audience. The researched texts demonstrate various methods for the implementation of solidarity tactics: messaging of information about commonality with the addressee; tactics of connection of the addressee to a joint action, declaration of support and empathy. We observe that the authors of the sermons carry out a purposeful selection of the language resources to implement the tactics of solidarity. The prospects for further researches are seen in the systematic study of a set of tactics used to implement the strategy of persuasion in the preaching discourse.